Pendampingan Pengawas Di Taman Kanak-Kanak Kecamatan Depok, Kabupaten Sleman, D.I. Yogyakarta - Zuliyahajh Zuliyahajh; Wiwik Wijayanti (SAP (Susunan Artikel Pendidikan), 2026)
This study aims to describe the mentoring process conducted by kindergarten supervisors in Depok District, Sleman Regency, D.I. Yogyakarta, and identify the challenges encountered during its implementation. A descriptive qualitative approach was employed, utilizing interviews, observations, and document analysis. The findings reveal that the mentoring process generally follows the framework of the Director General of Teachers and Education Personnel Regulation Number 4831/B/HK.03.01/2023 on the Role of School Supervisors in Implementing the Merdeka Belajar Policy in Educational Units, encompassing planning, implementation, and reporting stages. However, disparities were found in the frequency of school visits, with only a few sample schools receiving regular mentoring, while others were never visited. Key challenges include high supervisor workload due to an excessive number of schools under their supervision, geographical barriers hindering direct visits, resistance from senior teachers to change, and low information technology proficiency among educators. The implications underscore the need for workload redistribution among supervisors, leveraging digital technology for remote mentoring, enhancing teachers' technological capacity, and adopting a more persuasive and contextual approach to address resistance to change. Policy recommendations include adjusting the supervisor-to-school ratio and strengthening technology-based mentoring systems to ensure equitable access for all schools.